2017
DOI: 10.1111/1471-0528.14839
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of surgical interventions for women with FGM/C: a systematic review

Abstract: Systematic review shows defibulation after FGM/C has obstetric benefits; effect of reconstruction is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 32 publications
1
72
0
Order By: Relevance
“…A recent systematic review 61 evaluated the effects of reconstructive surgery. The results indicate that about three women out of four regain a visible clitoris; self-reported ameliorations in pain during sex, clitoral function/pleasure, orgasm, and desire are in the 43–63% range, but up to 22% reported a worsening in sexual outcomes.…”
Section: Reconstructive Surgerymentioning
confidence: 99%
“…A recent systematic review 61 evaluated the effects of reconstructive surgery. The results indicate that about three women out of four regain a visible clitoris; self-reported ameliorations in pain during sex, clitoral function/pleasure, orgasm, and desire are in the 43–63% range, but up to 22% reported a worsening in sexual outcomes.…”
Section: Reconstructive Surgerymentioning
confidence: 99%
“…Therefore, the authors concluded that FSFI is a suitable psychometric tool for conducting a standardized assessment of sexual function in women with FGM/C. A recent systematic review, which has included 62 studies (5829 women), has reported that up to 22% of women with FGM/C showed worsening of sexual function after CR [51].…”
Section: Discussionmentioning
confidence: 99%
“…The one woman who underwent elective antenatal de‐infibulation received thorough consultant‐led counselling. A meta‐analysis of the scarce evidence for surgical intervention for FGM showed that de‐infibulation is associated with a significantly lower risk of CS (relative risk 0.33) and severe perineal trauma however, women who are de‐infibulated during delivery may experience higher blood loss…”
Section: Discussionmentioning
confidence: 99%